Accounting disclosure of social responsibility and its impact on achieving sustainable development goals: (Applied research in the State Company for Food Industries- Diwaniyah Dairy Factory) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The researchers seek to shed light on the importance of accounting disclosure on social responsibility, and the research aims to provide a theoretical approach to social accounting and its disclosure, identify the concept of sustainable development, highlight the theoretical foundations of sustainable development and employ disclosure of social responsibility towards achieving the goals of sustainable development, and identify the impact of The accounting disclosure on social responsibility in achieving sustainable development goals, and the research problem can be reviewed by asking the following question (Does the accounting disclosure of the social responsibility of economic units contribute to achieving sustainable development?), And the research hypothesis was formulated to study the effect of the accounting disclosure of social responsibility on the sustainable development of the enterprise. The importance of the research stems from the importance of the role of economic units that are part of society, and accordingly, there is an urgent and necessary need to know the extent to which these units achieve their social responsibilities by disclosing the social contributions of the economic unit in a way that contributes to the possibility of achieving the goals of sustainable development, adopting the inductive approach ( Descriptive) in addressing research problems and proving His hypotheses are in the theoretical side to achieve the research objectives. As for the applied side, it is based on the approach (descriptive and analytical) to analyze the results of the questionnaire that was distributed to the members of the research sample as well as the personal interviews that were conducted with the relevant authorities, and among the most important results that were reached was the presence of influence A significant statistical significance between the accounting disclosure of social responsibility and its various activities and sustainable development.